Evolving Marketing Strategies of BRI: Digital Transformation Insights (2014-2024) - Citra Biola Lumbantobing; Mirwan Surya Perdhana (Arthatama: Journal of Business Management and Accounting, 2025)
This study examines the evolution of marketing strategies at Bank Rakyat Indonesia (BRI) from 2014 to 2024, focusing on the Relationship Manager Funding & Transaction (RMFT) team at the BSD Branch Office. As digital transformation accelerates and customer expectations rise, BRI has adapted its marketing approaches to become more innovative and customer-centric. Using a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA), the research gathers insights from RMFT personnel, service staff, and customers. Key findings reveal the importance of relational marketing, customer experience, and product innovation in boosting customer satisfaction and loyalty. The use of big data tools like BRISPOT Consumer has allowed BRI to personalize services and enhance strategic decision-making. This study highlights how BRI's marketing strategies have evolved in response to technological advancements and market demands, emphasizing the shift toward customer-oriented marketing innovation. Ultimately, it provides valuable insights for financial institutions aiming to stay competitive in the digital age. This research discusses the evolution of marketing strategies at Bank Rakyat Indonesia (BRI) in the context of digital transformation and how these strategies have been tailored to meet dynamic business needs. The shift toward customer-oriented marketing innovation and the use of big data for service personalization are aligned with the concept of sustainable digital transformation. This study contributes to the literature on banking marketing strategies and offers practical insights for financial institutions aiming to remain competitive in the digital era.